Advances in understanding the formation and fate of B-cell memory in response to immunization or infection. Issue 1 (11th September 2021) - Kealy, Liam; Good-Jacobson, Kim L
Abstract: Immunological memory has the potential to provide lifelong protection against recurrent infections. As such, it has been crucial to the success of vaccines. Yet, the recent pandemic has illuminated key gaps in our knowledge related to the factors influencing effective memory formation and the inability to predict the longevity of immune protection. In recent decades, researchers have acquired a number of novel and powerful tools with which to study the factors underpinning humoral memory. These tools have been used to study the B-cell fate decisions that occur within the germinal centre (GC), a site where responding B cells undergo affinity maturation and are one of the major routes for memory B cell and high-affinity long-lived plasma cell formation. The advent of single-cell sequencing technology has provided an enhanced resolution for studying fate decisions within the GC and cutting-edge techniques have enabled researchers to model this reaction with more accuracy both in vitro and in silico . Moreover, modern approaches to studying memory B cells have allowed us to gain a better appreciation for the heterogeneity and adaptability of this vital class of B cells. Together, these studies have facilitated important breakthroughs in our understanding of how these systems operate to ensure a successful immune response. In this review, we describe recent advances in the field of GC and memory B-cell biology in order to provide insight into how humoral memory is formed, as well as the potential for generating lasting immunity to novel pathogens such as severe acute respiratory syndrome coronavirus 2. Lay Summary: In light of the recent pandemic, the development and distribution of a safe and effective vaccine have become the primary objective for scientists, political leaders and policymakers the world over. The success of these vaccines is contingent on their ability to stimulate B-cells to form long-lived plasma cells, capable of producing protective antibodies against the novel coronavirus, as well as immune memory cells which provide enhanced and lasting protection upon re-exposure. However, beyond vaccines, we have a large gap in our capabilities to therapeutically target memory B cells. This review dissects recent technological advances that have revealed new insights into how immune memory is achieved. Understanding how we can unlock the potential to modulate memory B cells will increase our capacity to respond to newly emerging pathogens and variants in the future.